Simulation and effects analysis of region models for interior fire hazard - Luo, Tao; Cao, Chen (Revista de la Construcción. Journal of Construction, 2015)
The region model analysis is an important method for analyzing the interior fire hazard. Based on the mass conservation equation and energy conservation equation of the pre-flashover interior fire hazard development, the formulae required by computer programming are derived. VB is utilized as a tool for developing computation program with the aid of object programming idea to apply the mathematical modelling theories of the release rate of fire heat, plume and heat transfer. The relevant programming procedures and computation flow chart are presented. The program is verified through experimental data from Tianjin Fire Research Institute. As the computation of plumes is oversimplified, the thickness change of the smoke layer and the results obtained in the experiment vary considerably. The main advantage of the proposed computation model is that it is ease to be utilized for a variety of occasions.